Are green resource productivity and environmental technologies the face of environmental sustainability in the Nordic region?. (27th September 2022) - Alola, Andrew Adewale; Adebayo, Tomiwa Sunday
Abstract: This study examines whether the raw material productivity, export intensification, and environmental‐related technologies in the Nordic region (i.e., Denmark, Finland, Iceland, Norway, and Sweden) drives the region's carbon neutrality target. By adopting both symmetric and asymmetric empirical approaches over the period 1990–2019, the study found that positive and negative shifts in environmental‐related technologies mitigates greenhouse gas (GHG) emissions in the region with the former causing a larger impact. Furthermore, the findings reveal that a positive shift in raw material productivity mitigates GHG emissions while a negative shift in raw material productivity causes a surge in GHG emissions especially in the long‐run. Moreover, a positive (negative) shift in export intensity yields a decline (upsurge) in GHG emissions in the long‐run. In the symmetric framework, in both long‐ and short‐run, the result reveals that economic growth upsurges GHG emissions while raw material productivity for green growth and environmental‐related technologies mitigates GHG emissions. This demonstrates the efficient raw material productivity profile of the Nordic countries. Alongside the Granger causality inference, the result further informs that energy intensity is crucial to curbing GHG emissions in the region. Thus, the result from the study offers relevant policy instructions.